Червецы и щитовки — вредители сельскохозяйственных растений в западных областях Украины - Терезникова, Е.М. (Вестник зоологии, 1969)
Among the Coccoidea there are a considerable number of pests of various agricultural plants. In the western regions of the Ukraine these pests in mass reproduction cause great damages to agriculture. The following Coccoidea are the main pests of agricultural plants in the western regions of the Ukrainian SSR: Parthenolecanium corni В о u c h e, Sphaerolecanium prunastri F о n s c., Lepidosaphes ulmi L., Quadraspidiotus perniciosus С о m s t (distributed on a large scale); Phenacoccus aceris Sign., Eroipeltis agropyri В о r c h s., Quadraspidiotus spurcatus Sign., Quadraspidiotus ostreaeformis Curt, (frequent); Phenacoccopsis bufo К і r., Pseudococcus aberrant G о u x, Phenacoccus cholodkovskii March., Pulvinaria betulae L., Epidiaspis leperii Sign., (rare); Heliococcus cydoniae Borchs., Palaeolecanium bltuberculatum T a r g., Parthenolecanium persicae F., Eulecanium mail S c h r., Eule-canium tiliae L. (very rare).